Trustworthy Global Computing 6th International Symposium, TGC 2011, Aachen, Germany, June 9-10, 2011. Revised Selected Papers - Bruni, Roberto; Sassone, Vladimiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 6th International Symposium on Trustworthy Global Computing, TGC 2011, held in Aachen, Germany, in June 2011. The 14 revised full papers presented were carefully reviewed and selected from 25 submissions. The papers are organized in topical sections on modeling formalisms for concurrent systems; model checking and quantitative extensions thereof; semantics and analysis of modern programming languages; probabilistic models for concurrency; and testing and run-time verification.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Coding theory; Computer software; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Software Engineering; Coding and Information Theory